Analytical and numerical modeling for the assessment of CO2 storage in the Pariñas geological formation - Talara, Peru - Pomar-Castromonte, R.; Ingol-Blanco, E.; Santos, J.; Santa-Cruz, S. (Elsevier, 2021)
This research evaluates the CO2 storage capacity of the Pariñas Formation belonging to the Talara basin in Peru through analytical modeling based on mass balance equations and numerical modeling using IMEX CMG. Pariñas Formation has several depleted hydrocarbon reservoirs that presents favorable conditions for CO2 geological storage. It has an average porosity of 17.6% and a permeability of 640 mD in the horizontal direction consisting of sandstones with interspersed lutites layers. The study evaluates the depleted Bellavista oil deposits involving CO2 storage capacity estimation with CO2 and reservoir fluid (oil and water) interaction. It involves numerical modeling based on the reservoirs properties and CO2 injection simulation not exceeding the fracture pressure of the reservoir rock. This approach is the first one carried out in Peru and provides the chance to evaluate the CO2 storage capacity in a hydrocarbon reservoir in this part of the world, as a strategy to mitigate future global change impacts. The results indicate a storage capacity of 35.37 million tons of CO2, approximately. Besides, the sandstone reservoir of the Pariñas geological formation has adequate characteristics to serve as a CO2 storage reservoir. C30+ pseudo component shows greater sensitivity in its properties (temperature and critical pressure) adjusting the fluid properties with the experimental data (saturation pressure, viscosity and minimum miscibility pressure).
Keywords: CO2 injection; Parinas-Talara; Numerical modeling; CO2 storage; https://purl.org/pe-repo/ocde/ford#1.05.02